248 ETHNIC DIFFERENCES IN CYTOKINES EXIST IN RECENT-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS. (1st January 2006) - Jenkins, J. K.; Yacob, G.; Majithia, V.; Harisdangkul, V.; McMurray, R. W.
Abstract : Purpose: Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown etiology that affects young black women more severely than white women. Cytokines are a crucial factor in initiating, maintaining, and subsequently down-modulating the immune response in autoimmune disease. Significant ethnic differences in cytokines have not been reported. We investigated ethnic differences in TH1, TH2, and inflammatory cytokines in black and white women with recent-onset SLE. Methods: Healthy premenopausal women with SLE for less than 5 years were enrolled. A standardized disease activity measure (Systemic Lupus Activity Measure or SLAM) was performed, and a blood sample was taken to measure cytokine levels by ELISA. We measured the inflammatory cytokines IL-1b, IL-6, and TNFa; the TH1 cytokines IL-2 and IFNg; and the TH2 and anti-inflammatory cytokine IL-10. BD Biosciences assays were used, had less than a 15% inter- and intra-assay variability in our hands, and recovered 90-105% of spiked cytokine. Results: Thirty-three black and 14 white women were enrolled. The black women were slightly younger (31.6 vs 38.8 yr, p > .05) but clinical disease was similar. ACR criteria, SLAM score, and patient and MD global assessment were similar. TNF was not different between black and white women. Higher levels of IFNg (25.7 6 22.4 vs 18.3 6 18), IL-1 (31.2 6 44.1 vs 18.6 6 38.9), IL-2 (45.1 6 92.8 vs 12.1 6 9.5), and IL-6 (27.8 6 61.6 vs 10.2 6 10.6) were present in black than white women, respectively, but was not significant (p > .05). IL-10 was significantly lower in black (10.7 6 18.6) compared to white (29.8 6 25.4, p = .001) women. Conclusion: The propensity of young black females to earlier onset and more severe SLE may be due in part to the inadequate anti-inflammatory TH2 cytokine IL-10 in the presence of an enhanced inflammatory and TH1 cytokine profile.